Kajian Kebahasaan dan Makna Lirik Lagu Evaluasi Karya Hindia dalam Perspektif Sosial dan Psikologis - Gita Ayu Lestari Banurea; Nadia Citra Hutagalung; Siti Zahra; Rascya Alandra Simbolon; Ferdinand Simbolon (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2026)
This study examines the linguistic features, meanings, and social and psychological representations in the lyrics of the song “Evaluasi” by Hindia (Baskara Putra). A qualitative approach with a library research method was employed. The primary data consist of the official song lyrics, supported by theoretical frameworks in stylistics, semantics, discourse analysis, social representation, and literary psychology.The results show that the lyrics use expressive diction with both denotative and connotative meanings. Various stylistic devices, including metaphor, hyperbole, repetition, and personification, enhance the emotional depth of the song. The discourse structure is coherent, moving from emotional distress, to self-reflection, and finally acceptance.Denotative meanings reflect literal life experiences, while connotative meanings highlight emotional themes such as self-evaluation, psychological pressure, and social relationships. Socially, the song portrays challenges faced by young people, including identity struggles, social pressure, and mental health issues. Psychologically, it reflects emotional exhaustion, introspection, and self-acceptance. Overall, the study concludes that popular music functions not only as entertainment but also as a medium for social and psychological reflection in contemporary society.